A presença do cordel na literatura infantil : um estudo sobre Lampião & Lancelote, de Fernando Vilela - Pizani, Melissa Santana Nestorio (2010)
Current research analyzes Fernando Vilela's Lampião & Lancelote which includes folk song in its composition. The reader is interpellated by the text and provoked by issues referring to this type of literature which, albeit in print, develops orality, playfulness and popular culture. Although Folk Song Literature is one of our most important cultural heritages hailing from the Iberian Peninsula and in spite of its publications in booklets and the vast critical bibliography produced, it is actually almost ignored by the general public. Research is justified by the few productions and analyses on Folk Song Literature directed to the children and to young people. The Aesthetics of Reception and the Effect Theory, which treat the reader as a responsible agent who gives life and significance to the text, within the reading process, are the basis of current investigation. The theoretical concepts that underlie current research are those that analyze the effects that the literary text stimulates the reader. Since an intense relationship exists between the two poles, expectations are not merely enriched and deepened but also promote reflections. Results show that Lampião & Lancelote is an important and meaningful literary work, featuring unquestionable aesthetic and literary quality, spreading Folk Song Literature among children and young people, which warrants the active participation of the readers and contributes in their emancipatory formation. Besides its originality, Folk Song features such compositional and stylistic resources as meter, orality, captivating title, duels, meaning relationship among the rhyming words and others. The deep relationship between the text and images and the phrases which characterize medieval romances are made up from such aspects. Xylographs and illustrations worked out from wooden sketches in leaden colors, manufactured by the author, indicating the environment surrounding Lampião, and in silver, indicating the environment surrounding Lancelot, establish a meaningful relationship by which there is neither an autonomous text nor an independent illustration. Suspense, magic, humor, fantasy and the marvelous in the duels between the knight, medieval Europe, the Brazilian rural gangsters and the Brazilian northeastern hinterland promote mediation with the reader. Language, evidenced by playful features, is also an important mediation factor. Since Lampião & Lancelote lacks didactic and pedagogical aims and makes the readers form representations and adopt their point of view, it comprises contemporaneity in its approach to Children's Literature and Folk Song Literature.